Factors Affecting Competitiveness in the Construction Industry: A Systematic Literature Review - Al-Kayed, Anas; Rotimi, Funmilayo Ebun; Purushothaman, Mahesh Babu; Ghaffarian Hoseini, Ali; Purushothaman, Mahesh Babu (ISEC Press, 2024)
In today's globalized and highly competitive construction industry, it is crucial for companies to have a deep understanding of competitiveness in order to survive. The competitiveness of the construction industry is influenced by a multitude of factors. As a result, construction organizations must improve their understanding of the relationships between these various factors that affect competitiveness. Thus, this paper aims to determine the factors affecting competitiveness in the construction industry through an analysis of relevant literature focusing on aspects that shape competitiveness in the construction industry. This systematic review explores these factors by analyzing 27 peer-reviewed English-language articles from 2003-2023. It found that the major factors affecting competitiveness are mainly under eight main themes: technological, organizational, human resource, and strategic factors, economic and political factors, financial factors, operational factors, and external factors. The review emphasizes the growing importance of digital technologies in the construction industry's competitiveness and provides guidance for future studies.
Keywords: Competition; Digitalization; Globalization; Innovation; Knowledge.